A CASE REPORT OF BREAST CANCER TREATMENT IN TRANSGENDER MEN WITH BILATERAL SUBCUTANEOUS MASTECTOMY - Nunes, Mirella Laranjeira; Beltrão Neto, João Esberard de Vasconcelos; Araújo, Rossano Robério Fernandes; Santos, Ana Leide Guerra dos; Figueira, Guilherme Simão dos Santos (Mastology, 2021)
Introduction: The risk of breast cancer in transgender men is similar to that of cisgender women. The average age at diagnosis is 44 years, suggesting an early incidence with greater tumor aggressiveness. It commonly presents as a palpable mass, years after masculinizing mastectomy, and has a histological subtype of invasive ductal carcinoma and luminal molecular subtype. Although there are no screening and treatment protocols for these cases, similar follow-up to CIS is recommended, including mastectomy, hormone therapy, radiotherapy and chemotherapy. Case report: Patient, 42 years old, woman, transgender, nulliparous, no use of hormones, presented to an appointment asking for aesthetic mastectomy. She reported a family history of aunt and two cousins with breast cancer and a 32 year-old sister with atypical ductal hyperplasia. She identified a mass in the superolateral quadrant of the left breast through self-examination of the breasts. The mammography showed dense breasts, BIRADS 0. Breast ultrasound resulted in a solid, hypoechoic nodule, irregularly contoured, microlobulated, measuring 1.1x0.6 cm, between 2h and 3h, and about 3 cm from the areola of the left breast and BIRADS 5. Resonance imaging showed this hypointense nodule with lobulated contours measuring 1.3 x 0.6 cm, 3.3 cm from the nipple and 1.7 cm from the pectoral muscles. USG-guided thick needle biopsy diagnosed IDC (Invasive ductal carcinoma), histological grade 2, nuclear grade 3, with moderate stromal fibrosis, severe stromal elastosis, mild lympho- cytic inflammatory infiltratation and vascular invasion present. It was 100% positive estrogen receptor and 50% posi - tive progesterone receptor, with 12% Ki67 and negative HER-2, luminal molecular subtype A at immunohistochemistry. A bilateral skin and papillary areolar complex saving mastectomy was performed with sentinel node biopsy on the left. Anatomopathological examination showed absence of metastatic neoplasia in the lymph nodes and left breast with IDC in the retroareolar region, with the same characteristics as the previous biopsy. Pathological staging was T1N0M0 and anatomical staging and pathological prognosis was Ia. Oncotype DX Recurrence Score test was equal to 26. The patient was subjected to six cycles of Taxotere plus Cyclophosphamide and is using Tamoxifen and hormone with Androgel. We report a case of subcutaneous mastectomy used in an innovative way with preservation of the areola-papillary complex (APC), with an aesthetic contour of the chest wall and adjustment of the APC, allowing greater satisfaction in the experience of the genus. The same breast pathology that occurs in women should be expected in transgender women. So, we must consider that the focus on the aesthetic result may result in less precaution with the thickness of the remaining dermogreasy flap, with residual breast glandular tissue, and a higher risk of breast cancer.